Rancangan Website di Perpustakaan Museum Adityawarman Padang - Yetti, Gustia; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This article aims to reveal the systematic design of the website. Data were collected through observation and interviews with librarians. Data analysis was done descriptively. By analyzing the data, it was concluded matters as follows. (1) the design of websites using Adobe Dreamweaver CS3, (2) the information discussed in this paper about the website includes the steps of data collection by observation and interviews, process design websites with Adobe Dreamweaver CS3 as well as designing the header using applications Fireworks CS3 Portable, and (3) description of the scope of information is divided into seven key menu consisting of, first menu Home (congratulations came from the head of the museum), the second menu Profile (history, organizational structure, staff and vision), a third menu News (activity library), fourth menu Album (photo collection), the fifth menu Services (facilities and service time), the sixth menu Information (information about the library), and the seventh Contacts menu (comments and suggestions). Keywords: Design, website, library